Recasting forest forager and food-producer population interaction as a pivotal prehistoric process of change - Karen D. Lupo; Dave N. Schmitt (Afriques)
In the ethnographic and recent past, forested areas of West and Central Africa were populated by forest foragers and food producers who maintained multidimensional interrelationships. While the timing of the emergence of these interrelationships is unknown, forest forager-farmer interactions are rarely considered as a process of cultural or ecological change in the archeological record of Central Africa. Here we argue that Central African prehistoric forager-farmer interactions likely had far-reaching demographic, social, political, and ecological consequences that may have profound implications for the material record. Archaeological research focused on the spread of Bantu-speaking populations should consider the influence of indigenous forager populations on the spread and lifeways of migrating food and iron producers into forested regions. We advocate for the development and use of ethno-archaeological frameworks in identifying some of these interactions in the prehistoric record.